Nutritional, Phytochemical, and Antimicrobial Properties of Carica papaya Leaves: Implications for Health Benefits and Food Applications - Rajni Choudhary; Ravinder Kaushik; Ansab Akhtar; Suvendu Manna; Jyoti Sharma; Aarti Bains (Foods)
Background: Papaya leaves (PLs) are known for their therapeutic benefits and traditional use in treating inflammation, infections, and various health conditions. Rich in bioactive compounds, PLs are studied for their potential applications in functional foods. This study analyzed their nutritional, phytochemical, structural, thermal, and antimicrobial properties to evaluate their role as a health-promoting ingredient. Methods: Phytochemicals were quantified spectrophotometrically and identified via GC-MS. Antioxidant activity was assessed using DPPH and FRAP assays. Mineral content was determined using ICP-OES. Structural and thermal properties were evaluated using FTIR, XRD, and calorimetry, and antimicrobial activity was tested via the agar well diffusion method. Results: PLs contained 25.75% crude protein, 41.49% carbohydrates, and high levels of flavonoids (21.00 mg QE/g), phenolics (8.85 mg GAE/g), and tannins (430 mg TAE/g). Antioxidant assays confirmed strong free radical scavenging potential. Mineral analysis showed abundant K, Ca, Mg, Na, and Fe (4071, 1079, 789.2, 361.2, and 228.2 mg/kg, respectively). Structural and thermal analysis revealed bioactive functional groups, 23.9% crystallinity, and thermal degradation characteristics. PLs exhibited antimicrobial activity, inhibiting E. coli, S. aureus, B. subtilis, and K. pneumoniae with zones of 22.05–25.15 mm. Conclusions: PLs demonstrate strong nutritional, antioxidant, and antimicrobial properties, supporting their inclusion in functional food.